If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 3x = 58 Reorder the terms: 3x + 7y = 58 Solving 3x + 7y = 58 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 3x + 7y + -7y = 58 + -7y Combine like terms: 7y + -7y = 0 3x + 0 = 58 + -7y 3x = 58 + -7y Divide each side by '3'. x = 19.33333333 + -2.333333333y Simplifying x = 19.33333333 + -2.333333333y
| -3/7(2)-2=y | | 7+63y= | | 6p-8p+-5=-17 | | 55m+5= | | 7x+4+5x+3+2+5=180 | | .80(5-20x)=-44 | | (-3)^5/(-3)^8 | | 102=-3(6n-4) | | h(x)=(2x+5)(3x-1) | | 7^5/7^3 | | (-4)^8/(-4)^4 | | 8^4/8^0 | | -6x^2+11-13=0 | | (-3)^6/(-3)^8 | | (-8w+8)-(w-2)= | | 8cosx=6 | | -6w-(-4z+5w)+7z= | | 78x+31=90 | | 78x+31=180 | | y=-1+28x-171 | | (-2-n)+(6n-7)= | | 5+2(9x-4)=4x+7 | | 2(6-5x)+6=8-5x | | 9/5=x/20 | | y=-4x+28x-171 | | 40/64=10/t | | 25/12x=30 | | -11-3(2*-11-7)= | | 2(2x-9)-5=2(x-5)-3 | | 25-12x=30 | | 7x-(2x+17)=18 | | 49=7/8(v) |